Analysis of The Expectations of Gresik Residents in Searching for Tourist Information Through Hashtags and Geotags on Instagram - Syamsuddin, Roshif; Ulum, Ahmad Bahrul (Semantik: Journal of Social, Media, Communication, and Journalism, 2023)
This research aims to analyze the process of forming tourists' expectations through the use of information search features such as hashtags and geotags on the social media platform Instagram. Social media has transformed how information is disseminated and consumed through usergenerated content. On Instagram, users are not only passive consumers but also active providers and consumers of information. They can freely share their travel experiences through posts that are tagged with hashtags and geotags. By searching using hashtags and geotags, tourists' initial expectations are formed. This research utilizes a case study method with a qualitative approach, conducting interviews with 10 individuals through purposive sampling, and content analysis to examine the formation of tourist expectations through hashtags and geotags on Instagram. The results of the study indicate that user interaction through hashtags and geotags plays a crucial role in shaping expectations. Search features such as hashtags and geotags support the formation of tourists' initial expectations, encompassing the geographical overview of a place to nearby accommodations. Additionally, visually appealing content and information contained in tags or captions also play a vital role in users' decision-making